Կոստանդնուպոլսի հայ արծաթագործության մի նմուշ - Ֆլորա Ղազարյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Статья содержит подробный анализ Евангелии и оклада номер 879 Эчмиадзинского монастыря. На основе анализа и сравнения оригиналов в статье уточнена дата публикации Евангелии. Таким образом выясняется, что Евангелия была опубликована не в 1796 году, как считалось до этого, а первого марта 1797 года. The article contains a detailed analysis of the number 879 Gospel and its cover from the Holy Mother See of Etchmiadzin. Based on the analysis and the comparison of the original materials the article clarified the date of the publication of the Gospel. So it turns out that the Gospel was published not in 1796, as it was thought previously, but on March 1,1797.
Keywords: Bibliography; The Bible; Fine Arts; Illuminating of Manuscripts and Books